Closing the phosphorus cycle: Current P balance and future prospects in Germany. (1st May 2022) - Mayer, Natalie; Kaltschmitt, Martin
Abstract: Phosphorus (P) is one of the most important elements for life and at the same time a scarce mineral resource. To ensure long-term P availability, especially for agriculture, and to avoid negative environmental effects, sustainable P management is crucial. Against this background, this article aims to identify and quantify all significant P fluxes within Germany as a basis to reveal main P sinks and sources. Total P input into Germany sums up to over 300 ktP /a and the main P demand arises in agriculture with ca. 80% of total P demand. The major sink is P run-off from agricultural land into water bodies (180 ktP /a), which can be significantly reduced by improved fertilization procedures and the preservation of healthy soil conditions. By those measures, the use efficiency of both directly plant-available, inorganic P forms and organic P forms is enhanced. To provide targeted nutrient amounts by organic fertilizers, independent from the soil microfauna, and therefore replace added mineral fertilizers, one possible strategy is pre-treatment of manure before deployment with an overall potential of 122 ktP /a of inorganic P supply. Conditioning organic P in plant-based animal fodder into inorganic forms before feeding, as another measure, has two effects: firstly, it leads to enhanced nutritional availability of fodder P without the need for additional P supplements, and thereby secondly, significantly reduces P amounts in manure. Manure P is also rather shifted to mineral forms. This fodder pre-treatment provides an even higher P potential of 110–160 ktP /a. Other large sinks besides P run-off are P accumulation in sewage sludge (52 ktP /a) and P from slaughterhouse residues (100 ktP /a), both of which can be recovered with a theoretical potential of 124 ktP /a. The overall potential of the combined measures for P recovery and improved P availability has the capacity to cover the country's current entire mineral fertilizer P demand. Some of these measures have already been reinforced by legal regulations in recent years. However, sustainable P recirculation still requires more efforts in recovery and recirculation technology than today. Graphical abstract: Image 1 Highlights: 80% of all P demand occurs in agriculture. 15% of mineral P imports can be reduced through current restrictions. Slaughterhouse residues bear a recovery potential of 100 ktP /a in Germany. Conditioning of animal fodder and animal manure can mostly close the P balance.